The tenuous diplomacy of the Syrian conflict. Issue 2 (7th February 2016) - Unknown
Abstract : International diplomacy with respect to the Syrian conflict has been episodic and generally ineffective. Greater engagement by the Syrian regime and the passage of UN Security Council Resolution 2254 in support of negotiations on Syria's political transition have improved prospects for a political solution. But the parties remain far apart on the role of Syrian President Bashar al-Assad in a political transition, and therefore still face a steep uphill climb.